2002
DOI: 10.1098/rsta.2002.1103
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the offshore wave climate around the British Isles by satellite altimeter

Abstract: Satellite altimetry gives a new perspective on ocean wave climate. Measurements around the British Isles show a strong seasonality, with exceptionally large average wave heights to the west and north of the British Isles in the winter. Furthermore, the interannual variability of winter wave climate is very high. Most of this variability can be described by a strong linear dependence on the North Atlantic Oscillation (NAO) index. This relationship may largely explain observations of increasing wave heights in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 6 publications
1
28
0
Order By: Relevance
“…Table 1 establishes clear manifestations of the change in the NAO regime in the wind wave parameters in the North Atlantic. Woolf et al (2002) performed the EOF analysis of the altimeter SWH for 1985-99 using the data for the December-March period and obtained results very similar to our spatial patterns. Correlation of the first PC of SWH with NAO index was higher than 0.85.…”
Section: Interannual Variability In the Wind Wave Heightsmentioning
confidence: 54%
See 3 more Smart Citations
“…Table 1 establishes clear manifestations of the change in the NAO regime in the wind wave parameters in the North Atlantic. Woolf et al (2002) performed the EOF analysis of the altimeter SWH for 1985-99 using the data for the December-March period and obtained results very similar to our spatial patterns. Correlation of the first PC of SWH with NAO index was higher than 0.85.…”
Section: Interannual Variability In the Wind Wave Heightsmentioning
confidence: 54%
“…Quantitative comparison shows that our estimates are somewhat weaker than those reported by buoys that can be explained by the spatial averaging in a gridded product. Wave data from satellite altimetry Woolf et al 2002) provide relatively short time series. Comparison with them reveals quite good agreement of interannual variability and trends during the late 1980s and 1990s (Gulev et al 1998).…”
Section: Secular Changes In Wind Wave Heightsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the North Atlantic, for example, the interannual evolution of wave heights is related, at least partially, to climatic factors, such as the NAO index (The WASA Group 1998, Wolf & Woolf 2005. Woolf et al (2003) found that most of the interannual variability of winter wave climate around the British Isles can be related to the NAO. According to Lionello & Galati (2008), the EA pattern (Wallace & Gutzler 1981) has a greater influence on the variability of waves than the NAO over the western Mediterranean.…”
Section: Wave Climatementioning
confidence: 99%